Human Exposure to Asbestos in Central Asian Countries and Health Effects: A Narrative Review - Kurzhunbaeva, Zhyldyz; Dzhusupov, Kenesh; Spinazzè, Andrea; Visonà, Silvia Damiana; Sulaimanova, Cholpon; Kasymov, Omor; Belluso, Elena; Colosio, Claudio (La Medicina del Lavoro, 2024)
The discovery of the detrimental effects of asbestos on human health came long after its widespread use, with the first scientific evidence of asbestos-related diseases emerging in the late 19th and early 20th centuries. Despite efforts to ban its use, asbestos continues to be mined and used in Central Asia (as well as in Russia, China, and other countries). To gain a deeper understanding of the situation in Central Asia, we have conducted a systematic review of scientific literature on the use of asbestos, exposure assessment, and health consequences of asbestos exposure in this geographic area. This review encompasses studies about exposure assessments, epidemiological data, and biochemical or clinical surveys conducted in Kazakhstan, Uzbekistan, Tajikistan, Turkmenistan, and Kyrgyzstan. A total of 18 articles met the inclusion criteria, and their content is summarised in this review, which represents the first attempt to systematically examine research on asbestos and its impact on the health of workers and the general population in Central Asia countries, including literature published in Russian and English. The findings here highlighted the substantial limitations of the currently available knowledge about the impact of asbestos on health in this geographical area.